Telecommunications Reform in Cote d'Ivoire - Laffont, Jean-Jacques; N'Guessan, Tchetche (World Bank, Washington, DC, 2014)
This paper analyzes Cote d'Ivoire's experience with telecommunications liberalization and privatization. Cote d'Ivoire privatized its incumbent operator in 1997, and granted the newly privatized firm seven years of fixed-line exclusivity while introducing "managed competition" in the cellular market and free competition in value-added services (VAS). By March 2001, three cellular operators and a number of VAS providers had entered the market. Reform has thus significantly changed the landscape of Cote d'Ivoire's telecommunications sector and has brought with it tremendous improvement in sector performance. Between 1997 and 2001, fixed-line telephone penetration grew from 1.03 to 1.80 per hundred people, while mobile penetration skyrocketed from 0.26 to 4.46. But it is still too early to assess the validity of granting exclusivity to the incumbent operator. While penetration increased, the operator did not meet objectives regarding rural telephony and service quality. Moreover, fixed-line penetration increased in areas where the operator faced competition from mobile providers.